2022
DOI: 10.1136/bmjopen-2021-059041
|View full text |Cite
|
Sign up to set email alerts
|

NIH funding of COVID-19 research in 2020: a cross-sectional study

Abstract: ObjectiveThis study aims to characterise and evaluate the National Institutes of Health’s (NIH’s) grant allocation speed and pattern of COVID-19 research.DesignCross-sectional study.SettingCOVID-19 NIH RePORTER Dataset was used to identify COVID-19 relevant grants.Participants1108 grants allocated to COVID-19 research.Main outcomes and measuresThe primary outcome was to determine the number of grants and funding amount the NIH allocated for COVID-19 by research type and clinical/scientific area. The secondary … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…COVID-19, however, was not the exclusive topic driving growth in scholarly activity during this time. For example, <5% of the NIH budget was allocated to COVID-19–related research in 2021 36 . Furthermore, an analysis of 10 high-impact medical and infectious disease journals found that in 2020, COVID-19–related publications accounted for 25% of research publications 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19, however, was not the exclusive topic driving growth in scholarly activity during this time. For example, <5% of the NIH budget was allocated to COVID-19–related research in 2021 36 . Furthermore, an analysis of 10 high-impact medical and infectious disease journals found that in 2020, COVID-19–related publications accounted for 25% of research publications 26 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, <5% of the NIH budget was allocated to COVID-19-related research in 2021. 36 Furthermore, an analysis of 10 high-impact medical and infectious disease journals found that in 2020, COVID-19-related publications accounted for 25% of research publications. 26 This was similar to our analysis of medical schools' experiencing the most rapid growth in publications, in which most of this growth was not driven by the number of articles produced about COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, a mere 2% of NIH's external grant funding went to covid-19 research, and only a handful of these grants were related to disease transmission or nonpharmaceutical interventions. 35 Furthermore, US research policy had, by the time of the pandemic, produced generations of public health scientists with little experience in public health practice. While there are notable exceptions of academic engagement with health departments, 36 little has changed since a 1988 Institute of Medicine report identified the separate silos of academic public health and government agencies as a problem.…”
Section: Public Health Research: Funded Publicly Pursued Privatelymentioning
confidence: 99%
“…Bush and others noted that the fact that OSRD was a new agency, with clear lines of command and little red tape, allowed it to move quickly. During the COVID-19 crisis, agencies including the NIH were unable to pivot as quickly to focus on new problems (Balaguru et al 2022), in part because of dominance of the investigator-initiated peer review model in biomedicine, but also due to the bureaucratic hurdles that are now associated with grantsmanship.…”
Section: The Osrd Model For Crisis Randd: the Case Of Covid-19mentioning
confidence: 99%